2018
DOI: 10.21608/jppp.2018.41303
|View full text |Cite
|
Sign up to set email alerts
|

Potency of some Photosensitizing Compounds against the Cotton Leaf Worm, Spodoptera littoralis (Boisduval) in Relation to some Biochemical Aspects

Abstract: The present study aimed to evaluate the toxicological as well as biochemical effects of the three photosensitizer compounds; rose bengal, eosin yellow lactone and methylene blue on the fourth larval instar of the cotton leaf worm, Spodoptera littoralis (Boisd.). Results of insecticidal activity against the fourth larval instar of S. littoralis revealed that rose bengal is the most toxic photosensitizer compound followed by eosin yellow lactone, then methylene blue. The corresponding LC 50 values were 37X10-5 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…In addition, reduction % (-47.07 and -25.27%) at LC25 and LC50 treatments, respectively. Our results agree with El-Ghobary, et al, (2018) who stated that the treatment with rose bengal, eosin yellow lactone and methylene blue, showed a significant reduction -40.37%, -17.31 and -18.29%, respectively in total lipids compared with control. The total lipids are essential as a resource of energy in insects.…”
Section: Field Experimentalsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, reduction % (-47.07 and -25.27%) at LC25 and LC50 treatments, respectively. Our results agree with El-Ghobary, et al, (2018) who stated that the treatment with rose bengal, eosin yellow lactone and methylene blue, showed a significant reduction -40.37%, -17.31 and -18.29%, respectively in total lipids compared with control. The total lipids are essential as a resource of energy in insects.…”
Section: Field Experimentalsupporting
confidence: 93%
“…Photooxidation of tyrosine with methylene blue involves the break of the circle and configuration of CO2 (Attia, 2016). Our result agrees with El-Ghobary, et al, (2018) who proved that the treatment with LC50 of photosensitizer compounds caused decreased in the total lipids, total protein and total carbohydrates content of S. littoralis, while methylene blue slightly increased total proteins compared with control. Other studies in the same field mentioned the effect of LC50 value of rose bengal on the adults' flies and the untreated control showed a significant decrease in the total protein content (Attia, 2016).…”
Section: Field Experimentalsupporting
confidence: 92%
See 1 more Smart Citation
“…The arbitrary expenditure of organic chemical pesticides led to the development of tick resistance and environmental pollution; there are great challenges to using affordable alternatives to reduce the risks to humans, non-target organisms and the environment [11][12][13][14][15]. Plantbased pesticides [16] and photosensitizer are efficient substitutes to the ordinary conventional pesticides and might be environmentally sound [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Methylene blue was more toxic than hematomporphyrin on S. littoralis (Abd El-Naby, 2007). In contrast, El -Ghobary, et al, (2018) found that methylene blue was being less effective against the 4 th larval instar of S. littoralis by recording larval mortality 29.50 % with concentrations 78X10 -5 M and 89.50 % with 391X10 -5 M. in these fields of study, Junqueira et al (2002) and Tardivo et al (2015) recorded that rose bengal was the most poisonous photosensitizer of used compound followed by eosin yellow. In addition, methylene blue is playing an important role in photodynamic therapy as a drug in vivo and in vitro of the living cells.…”
Section: A Toxicity Of Safranin Methylene Blue and Bromophenol Blue Against The 4 Th Larval Instars Of Agrotis Ipsilonmentioning
confidence: 97%